A series of CuII–LnIII complexes of an N2O3 donor asymmetric ligand and a possible CuII–TbIII SMM candidate in no bias field. (5th December 2018) - Mahapatra, Prithwish; Koizumi, Naoki; Kanetomo, Takuya; Ishida, Takayuki; Ghosh, Ashutosh
Abstract : Among four isostructural heterometallic Cu II –Ln III complexes (Ln = Tb, Dy, Ho or Er) of an N2 O3 donor asymmetric ligand, only the Cu II –Tb III complex shows SMM behavior at zero bias field but at applied bias field both the Cu II –Tb III and Cu II –Dy III complexes show SMM behavior. Abstract : A new series of four heterometallic Cu(ii )–Ln(iii ) complexes [where Ln = Tb (1Tb ), Dy (2Dy ), Ho (3Ho ) or Er (4Er )] has been synthesized using a Cu(ii ) metalloligand of an N2 O3 -donor asymmetric ligand H2 L (H2 L = N -α-methylsalicylidene- N ′-3-methoxysalicylidene-1, 3-propanediamine) and structurally characterized. All these complexes are isostructural and consist of dinuclear [(CuL)Ln(NO3 )3 ] units. The Ln(iii ) ions are nona-coordinated and the Cu(ii ) ions are tetra-coordinated with distorted square planar geometry in all the complexes. The DC magnetic susceptibility and field dependent magnetization measurements reveal that the Cu(ii ) and Ln(iii ) centres are ferromagnetically coupled in complexes1Tb and2Dy . In the AC magnetic susceptibility measurements at zero bias field, 1Tb exhibits an appreciable slow magnetic reorientation below 10 K with an effective energy barrier of approximately 17 K. Complex3Ho shows a slight increase in out-of-phase susceptibility below 4 K. With an applied DC field of 2000 Oe, both1Tb and2Dy display slow magnetic reorientation with effective energy barriers of 28.5(5) and 53(2) K, respectively.